1978
DOI: 10.1002/pssa.2210500114
|View full text |Cite
|
Sign up to set email alerts
|

Raman study of the phase transition in the CT-crystal anthracene-TCNB

Abstract: The Raman spectra of the CT‐crystal anthracene‐TCNB are investigated in the temperature range between 10 and 300 K. The orientational phase transition of the crystal at 206 K is observed from the temperature dependence of the resonance frequencies, intensities, and linewidths. It is shown that the low‐temperature structure is ordered and that a superstructure is formed. An assignment of some modes on the basis of isotropic shift and preresonance enhancement data is presented. Especially the frequencies of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This analogous behaviour is observable in the Raman spectra, too. A new mode appears at the transition temperature, and its linewidth exhibits a similar dependence on temperature as the corresponding mode of Anth-TCNB [13]. This is demonstrated in Fig.…”
Section: Anth075phen025-tcnbsupporting
confidence: 62%
“…This analogous behaviour is observable in the Raman spectra, too. A new mode appears at the transition temperature, and its linewidth exhibits a similar dependence on temperature as the corresponding mode of Anth-TCNB [13]. This is demonstrated in Fig.…”
Section: Anth075phen025-tcnbsupporting
confidence: 62%
“…A number of experimental studies have been carried out on this material using x-ray-diffraction 2-4 electron-paramagnetic-resonance ͑EPR͒ spectroscopy, 5 Raman-scattering spectroscopy, 6,7 and more recently Brillouin-scattering spectroscopy. 8 Results of these measurements have led to some controversy about the nature of the dynamical regime of the SPT.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion was favored by the absence of any soft phonon observation in the low-frequency part of the Raman spectra. 6 However, another more recent Raman study performed on oriented single crystals of high optical quality has revealed the existence of a soft optical mode ͑SM͒. 7 This mode has seemed to vanish about 15 K below the transition temperature (T c ).…”
Section: Introductionmentioning
confidence: 99%